Factors predicting collaborative willingness of surrogates making medical decisions on the Physician Order for Scope of Treatment (POST). (1st September 2020) - Spalding, Rachael; Edelstein, Barry
Abstract: Objective: The Physician's Order for Scope of Treatment (POST) indicates patient preferences regarding cardiopulmonary resuscitation (CPR), levels of care, and fluids/nutrition provision decisions. When patients become incapacitated, 'surrogates' often collaborate with physicians on POST decisions. Surrogates may vary in their willingness to collaborate, which can be problematic when physicians expect shared decision-making. No research has yet investigated collaborative decision-making among surrogates on the POST. This study investigated how six psychological variables predicted participants' desires for collaboration when completing an online decision-making task. Methods: Participants served as hypothetical surrogates and made decisions for another person on the three sections of the West Virginia POST. One-hundred-and-seventy-two adults were recruited from Amazon Mechanical Turk. Results: The six variables contributed significantly to the prediction of collaborative willingness, F (6, 163) = 5.29, p < .001, R 2 = 0.19. Two variables uniquely contributed: confidence and consideration of future consequences. The model most strongly predicted collaborative willingness for the CPR decision. Conclusion: This study provides a novel examination of under-researched areas: surrogate collaborative willingness and the POST. Differing risks associated with the three POST decisions may influence how surrogates value collaboration. Ways to enhance collaborative willingness when making POST decisions are discussed.